Possible Interrelations of the Proto-slavic Concept of “Fool” with Initiation Rites and Magic Fairy Tales - Olena Masliy (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
In a series of publications, the second of which is this article, the author attempts to explore the phenomenon of conceptual memory as a type of collective memory and cultural memory, as well as a way of accumulating significant meanings.